Determination of Community-Based Health Microinsurance Premiums Based on Health Costs - Shindi Adha Gusliana; Dwi Susanti; Sukono Sukono (International Journal of Research in Community Services, 2023)
Low-income households are faced with the financial risk of paying large medical bills when a member of the household falls ill. This health-related risk can affect household welfare because meeting medical expenses has the potential to reduce income capacity. Community-based health insurance is seen as one mechanism for vulnerable low- and middle-income households to overcome barriers and to improve access to health care and financial protection. This research was conducted to determine the calculation of community-based health microinsurance premiums based on health costs and determine the average willingness to pay insurance premiums. The determination of the premium is calculated based on the pure premium and other costs. Data obtained based on surveys and data provided by health facilities. Based on the results of the research, the pure individual premium is IDR 92,297.12 per year. The total individual premium calculated based on pure premium and other costs is IDR 275,256.80 per year. If the premium is paid monthly, a premium of IDR 22,938.07 per month will be obtained. Then the average value is obtained WTP or willingness to pay IDR 38,368.42 per month. The average value of the willingness to pay is greater than the total monthly health micro insurance premium that has been determined.